2018
DOI: 10.1016/j.bjm.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Rubber gloves biodegradation by a consortium, mixed culture and pure culture isolated from soil samples

Abstract: An increasing production of natural rubber (NR) products has led to major challenges in waste management. In this study, the degradation of rubber latex gloves in a mineral salt medium (MSM) using a bacterial consortium, a mixed culture of the selected bacteria and a pure culture were studied. The highest 18% weight loss of the rubber gloves were detected after incubated with the mixed culture. The increased viable cell counts over incubation time indicated that cells used rubber gloves as sole carbon source l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
7
31
0
Order By: Relevance
“…Natural rubber latex gloves can be disposed of by either landfill or incineration, which are not harmful to the environment. Recently, it was shown that the mixed culture isolated from soil samples collected from rubber contaminated ground in Songkhla province, Thailand had potential in degrading rubber, in which significant changes could be detected within 30 days [38]. In this study, the biodegradability of BC and the NR–BC films in soil is shown in Figure 11 and Figure 12.…”
Section: Resultsmentioning
confidence: 69%
“…Natural rubber latex gloves can be disposed of by either landfill or incineration, which are not harmful to the environment. Recently, it was shown that the mixed culture isolated from soil samples collected from rubber contaminated ground in Songkhla province, Thailand had potential in degrading rubber, in which significant changes could be detected within 30 days [38]. In this study, the biodegradability of BC and the NR–BC films in soil is shown in Figure 11 and Figure 12.…”
Section: Resultsmentioning
confidence: 69%
“…These carbon sources can easily be utilized by bacteria and accelerate their growth during lag phase. Some studies have revealed that the use of mixed bacterial culture (consortium) resulted in enhanced degradation of pollutants as mixed bacterial culture follows co-metabolism for pollutant degradation (Nawong et al, 2018; Tian et al, 2018). Li et al (2017) used four microorganisms including Roseateles terrae , Bacillus sp., Escherichia coli , and P. fluorescens , in a mixed culture for paraquat degradation, and achieved 97% degradation of initial paraquat dose (100 mg/L) over 7 days.…”
Section: Microbial Degradation Of Paraquatmentioning
confidence: 99%
“…35Y) and R. gummiphilus NS21 have the ability to form clearing zones on polyisoprene latex agar (Jendrossek et al 1997 ; Braaz et al 2004 ; Rose et al 2005 ; Imai et al 2011 ). Interestingly, other potent rubber degraders such as Gordonia polyisoprenivorans VH2, Gordonia westfalica Kb2, Nocardia farcinica , Nocardia nova SH22a and Rhodococcus rhodochrous RPK1 or Rhodococcus pyridinivorans F5 do not form clearing zones on latex agar (Ibrahim et al 2006 ; Warneke et al 2007 ; Bröker et al 2008 ; Luo et al 2014 ; Watcharakul et al 2016 ; Nawong et al 2018 ). Non-clearing zone-forming rubber degraders grow adhesively on the rubber surface and produce no visible clearing zone as shown by electron microscopy (Linos et al 2000 ).…”
Section: Rubber-degrading Bacteriamentioning
confidence: 99%